Effectiveness of a Yoga program in improving self-esteem and self-image of the elderly - Juliano Silveira Guimarães; Fabrício Bruno Cardoso; Alisson Padilha de Lima (Desafio Singular, 2020)
This study aimed to evaluate the effectiveness of a Yoga program in improving the self-esteem and self-image of the elderly. Thirty-six elderly individuals were evaluated, divided into two groups. The program lasted 2 months and was practiced 3 times a week, with a duration of 60 minutes each class. A structured and validated questionnaire was used to assess self-esteem and self-image. The elderly had a mean age of 60.5 ± 2.86 years, height of 1.66 ± 0.03 meters, and body mass of 69 ± 5.17 kg. For self-image an F = 52.36 was verified; p<0.001 and for self-esteem F = 48.78; p<0.001. It can be concluded in this research that the practice of yoga is effective in improving the levels of self-esteem and self-image of the elderly, it can be used through the therapeutic effects of exercise in the non-pharmacological treatment and prophylaxis of some psychiatric illness such as depression.